2023
DOI: 10.1021/jacs.3c09127
|View full text |Cite
|
Sign up to set email alerts
|

Correction to “Metal-Free Amino(hetero)arylation and Aminosulfonylation of Alkenes Enabled by Photoinduced Energy Transfer”

Xu-Kuan Qi,
Meng-Jie Zheng,
Chao Yang
et al.

Abstract: In Scheme 3, as well as in the Supporting Information, the structures of compounds 75−79 were drawn incorrectly. The structures of these five products obtained are actually derived from oxyimination reaction of alkenes without decarboxylation. 1 The corrected structures of 75−79 are shown below in the updated Scheme 3, and a revised Supporting Information file is provided with the updated data for compounds 76a−79a and 77b. Scheme 3. Substrate Scope of (Hetero)aryl Radical Precursor a,b a Reaction conditions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In the past decade, visible light catalysis has witnessed a remarkable accomplishment through the introduction of energy transfer processes (EnT) and electron transformations. [63][64][65][66][67][68][69][70] Speaking of energy transfer processes in the context of the present work, the excited photosensitizers are known to transfer its energy to ground-state molecular oxygen ( 3 O 2 ) to generate singlet oxygen ( 1 O 2 ), to attain selective chemical transformations. [71][72][73] Also, literature precedents suggested that quinoxalin-2(1H)-ones could assist energy transfer to ground-state molecular oxygen ( 3 O 2 ) to generate a singlet oxygen ( 1 O 2 ), to accomplish the chemical conversions.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, visible light catalysis has witnessed a remarkable accomplishment through the introduction of energy transfer processes (EnT) and electron transformations. [63][64][65][66][67][68][69][70] Speaking of energy transfer processes in the context of the present work, the excited photosensitizers are known to transfer its energy to ground-state molecular oxygen ( 3 O 2 ) to generate singlet oxygen ( 1 O 2 ), to attain selective chemical transformations. [71][72][73] Also, literature precedents suggested that quinoxalin-2(1H)-ones could assist energy transfer to ground-state molecular oxygen ( 3 O 2 ) to generate a singlet oxygen ( 1 O 2 ), to accomplish the chemical conversions.…”
Section: Introductionmentioning
confidence: 99%